INFORMATION SPACE FORMATION IN UKRAINE AS A BASIS FOR INCREASING THE PERFORMANCE OF PUBLIC AUTHORITIES ’ACTIVITIES - Nikitenko , Oleksiy (Theory and Practice of Public Administration, 2019)
One of the main factors in the development of the public administration system in Ukraine is the formation of a single information space tha twill improve the quality, efficiency and effectiveness of all public authorities. Today, an active process of forming such a component of the single information space of Ukraine in the sphere of activity of public authorities is taking place. At the same time, there is no scientifically substantiated concept of forming a single information space. This deprives the lawmaking work of the necessary theoretical basis, and in practice does not allow the full use of regional-level schemes for informational interaction with citizens, between public authorities and other organizations. Recent research and publications analysis. Issues of the information space are paid quite a lot of attention in the scientific literature. The scientific works by A.B.Aver’yanov, Yu.P.Bytyak, V.M.Bryzhko, O.A.Banchuk, A.M. Gulemin, S.F. Gutsu, E.V. Dodin, V.L. Ortyns’ky, O.I. Ostapenko, I.M. Pakhomov, A.A. Pukhtetska, V.S. Tsymbalyuk, Yu.S. Shemshuchenko, H.P. Yarmakita, etc. are devoted to a separate study of this problem. However, despite rather extensive and thorough studying, further research on the impact of the information space on the activities of public authorities is needed. Aim of the research is to determine the approaches to the formation of the information space in Ukraine, its structure and role, which it plays in improving and enhancing the performance of public authorities. Main paper body. In the context of the information society development, information becomes the main and integral attribute of social management in general, and management of information is considered as its part. Information management and information processes management form the core of the state’s information policy. Accordingly, the development of the information society, the formation of a state information policy, a systemically organized information space is a way both for economic well-being and for ensuring the country’s security. The key point is the development of the philosophy and ideology of an information society building. Scientists understand different concepts under the term "information space". For example, this may be a set of information infrastructure and resources, or satisfaction of information needs. Single information space consists of the following main components: information resources; information and telecommunication infrastructure; territorially distributed state and corporate computer networks, telecommunication networks and systems of special purpose and general use, networks and channels of data transmission, switching facilities and information flow management; information, computer and telecommunication technologies; scientific and production potential in the fields of communication, telecommunications, computer science, computer technology, distribution and access to information; organizational structures, in particular personnel providing the functioning and development of the national information infrastructure; the market of information technologies, communication facilities, informatization and telecommunications, information products and services; systems of interaction of the information space of Ukraine with the world’s open networks; information security systems (security); the mass media system; information law systems. Conclusions from the research and prospects for further exploration. So far, the current state of Ukraine’s information space is preventing its equal access to the world information society. Work on the development of information space in the leading countries of the world has been conducted at the initiative and under the patronage of senior state officials. Therefore, the formation and development of a single information space of Ukraine and relevant state information systems should be carried out at inter-branch and interregional levels with the use of an integrated, systematic approach to solving legal, organizational and technical issues. Implementation of new technologies and improvement of information legislation should be based not only on the needs of optimization of the internal activity of a separate government body, but also on improving the efficiency of interagency cooperation and the provision of public services. At the same time, it is necessary to determine the cooperation in the information sphere with other states and international organizations, which will make possible integration of the Ukrainian information space into the world information space. There search of these issues will be the priority for further investigation.